2018
DOI: 10.3389/fgene.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response and Prediction Characteristics of a Methylation Sensitive Digital PCR Assay for Cigarette Consumption in Adults

Abstract: The tobacco use disorders are the largest preventable cause of morbidity and mortality in the world. A substantial barrier to the development of better intervention and screening measures is the lack of clinically employable biomarkers to detect the existence and extent of tobacco consumption. In prior work, we and others have shown that array based assessment of DNA methylation status at cg05575921 is a sensitive and quantitative method for assessing cigarette consumption. Unfortunately, in general, arrays ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
3
41
2
Order By: Relevance
“…However, the most interesting finding from this study was that, on average, PTSD cases, relative to controls, had lower methylation at several CpG sites in the AHRR gene when compared to trauma-exposed controls. Methylation of AHRR CpGs has been strongly linked to smoking [29][30][31] . As substantially more of the PTSD cases reported smoking compared to controls, this suggested that we should control for smoking in the EWAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most interesting finding from this study was that, on average, PTSD cases, relative to controls, had lower methylation at several CpG sites in the AHRR gene when compared to trauma-exposed controls. Methylation of AHRR CpGs has been strongly linked to smoking [29][30][31] . As substantially more of the PTSD cases reported smoking compared to controls, this suggested that we should control for smoking in the EWAS.…”
Section: Discussionmentioning
confidence: 99%
“…) and cigarette consumption (Philibert et al . ). These findings suggest that DNA methylation changes at cg05575291 and cg03636183 can be reliably detected and have long‐term stability as measures of smoking exposure.…”
Section: Introductionmentioning
confidence: 97%
“…Whereas most smoking-associated CpGs demonstrate delta betas of less than 10%, in heavy smokers methylation at cg05575921 may be 50% or more below the population average of around 85%-90% [30]. This large dynamic range also facilitates the measurement of dose-response effects [28,[33][34][35] and reversibility of cg05575921 hypomethylation associated with smoking cessation [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%